Hyperactivity of medial prefrontal cortex pyramidal neurons occurs in a mouse model of early-stage Alzheimer’s disease without β-amyloid accumulation - Choudhury, Nasreen; Chen, Lihua; Al-Harthi, Lena; Hu, Xiu-Ti (Frontiers in Pharmacology, 2023)
The normal function of the medial prefrontal cortex (mPFC) is essential for regulating neurocognition, but it is disrupted in the early stages of Alzheimer’s disease (AD) before the accumulation of Aβ and the appearance of symptoms. Despite this, little is known about how the functional activity of medial prefrontal cortex pyramidal neurons changes as Alzheimer’s disease progresses during aging. We used electrophysiological techniques (patch-clamping) to assess the functional activity of medial prefrontal cortex pyramidal neurons in the brain of 3xTg-Alzheimer’s disease mice modeling early-stage Alzheimer’s disease without Aβ accumulation. Our results indicate that firing rate and the frequency of spontaneous excitatory postsynaptic currents (sEPSCs) were significantly increased in medial prefrontal cortex neurons from young Alzheimer’s disease mice (4–5-month, equivalent of <30-year-old humans) compared to age-matched control mice. Blocking ionotropic glutamatergic NMDA receptors, which regulate neuronal excitability and Ca2+ homeostasis, abolished this neuronal hyperactivity. There were no changes in Ca2+ influx through the voltage-gated Ca2+ channels (VGCCs) or inhibitory postsynaptic activity in medial prefrontal cortex neurons from young Alzheimer’s disease mice compared to controls. Additionally, acute exposure to Aβ42 potentiated medial prefrontal cortex neuronal hyperactivity in young Alzheimer’s disease mice but had no effects on controls. These findings indicate that the hyperactivity of medial prefrontal cortex pyramidal neurons at early-stage Alzheimer’s disease is induced by an abnormal increase in presynaptic glutamate release and postsynaptic NMDA receptor activity, which initiates neuronal Ca2+ dyshomeostasis. Additionally, because accumulated Aβ forms unconventional but functional Ca2+ channels in medial prefrontal cortex neurons in the late stage of Alzheimer’s disease, our study also suggests an exacerbated Ca2+ dyshomeostasis in medial prefrontal cortex pyramidal neurons following overactivation of such VGCCs.